EVOLUTION OF COMMUNICATION SOCIOLOGY: SOCIAL MEDIA INTERVENTION IN THE REALITY CONSTRUCTION OF SECOND ACCOUNT PHENOMENON IN THE ERA OF DIGITAL SOCIETY - Al-Haadi, Muhammad; Junisa, Salwa; Irsalina, Aulia; Chibro, Najeeda Emira (OPINI: Journal of Communication and Social Science, 2025)
This study investigates the sociological evolution of communication within the digital society, focusing on the phenomenon of second accounts as a strategic response to the social pressures prevalent on primary social media platforms. Using a qualitative methodology and virtual ethnography approach, the research aligns with the constructivist paradigm, aiming to deeply understand how individuals navigate and construct their social identities in digital spaces. Data sources encompass a comprehensive collection of academic books, peer-reviewed journals, and scholarly articles that discuss the nuances of digital communication and identity construction. Data collection methods integrate virtual observation and in-depth interviews, capturing the authentic experiences of individuals who maintain second accounts. Analytical techniques are guided by thematic analysis, emphasizing the identification and interpretation of patterns related to digital identity and social interaction. Data validity is ensured through triangulation, comparing observational data, interview transcripts, and existing literature to affirm the consistency and reliability of the findings. The study reveals that secondary accounts serve as a crucial medium for individuals to express their genuine selves, free from the curated personas often necessitated by primary accounts. This practice not only reflects a tactical management of social visibility but also illustrates a complex negotiation between personal freedom and social conformity. In conclusion, the research highlights the dynamic nature of digital identities, shaped by ongoing interactions within social media ecosystems. Second accounts emerge as a significant social phenomenon, allowing individuals to craft segmented identities that offer respite from the public gaze, thus enriching our understanding of modern communication practices in the digital era.